IMPLEMENTASI OTONOMI DESA DALAM MEWUJUDKAN PEMBERDAYAAN APARATUR PEMERINTAH DESA DODAGA DI KECAMATAN WASILE TIMUR KABUPATEN HALMAHERA TIMUR - NGAJI, BOEL; Rumapea, Patar; Rompas, Sonny (Sam Ratulangi University, 2016)
Abstract: The purpose of this study was to determine the ability of government officials in the village of EastHalmahera desa.Penelitian implementation of autonomy affairs is using qualitative methods. The government'sability village visits dar three indicators namely; education, training, and experience. Informants were takenfrom the village government elements Dodaga (village head and village secretary), in the village, the communityleaders / religious / cultural. The total number of informants who were interviewed are as many as 8 people.Collecting data using interview techniques, while the data were analyzed using qualitative analysis interactivemodel of Miles and Hubernann.The results showed: (1) Ability apratur village government Dodaga seen from indicators of education is quitegood, but not optimally. (2) The ability of the government apparatus village seen from the indicators of trainingis not maximized because not breathing is done either from the village administration or support you e heGovernment area . (3) The ability of the government apparatus Dodaga seen from the village of indicatorexperience thus even this is not too maximal.Based on these results ditarikkesimpulan that the capacity of Government officials in the implementation of theaffairs of the village of village autonomy in general has been running well but not maximum Deagan seen fromindicators of education, training, and experience.Based on the results of the research, put forward some suggestions to improve the government's ability toimplement urusan otonomi Dodaga Rural villages, as follows: (1) The village government should be allocatedsufficient budget to finance programs and activities. (2) The provision and improvement of infrastructure andfacilities Dodaga village government work needs to be done; and (3) Employee / village government officialsDodagaperluditambah, andquality SD officials / employees also need to be improved through education,training and experience relevant / program pemberdayaan.Keywords: Implementation of Village Autonomy in Delivering Government Apparatus Empowerment village